Bio-protective effect of a root-nodulating Rhizobium etli strain in common bean (Phaseolus vulgaris) against Meloidogyne incognita and Radopholus similis in an in vitro autotrophic tripartite culture system - Veken, L. van der; Win, P.P.; Seeboruth, P.; Cabasan, M.T.N.; Swennen, Rony L.; Elsen, A.; Waele, D. de (Brill, 2020)
The bio-protective effect of a root-nodulating strain (CNPAF 512) of the nitrogen-fixing rhizobium, Rhizobium etli, against both a sedentary (Meloidogyne incognita) and a migratory (Radopholus similis) endoparasitic nematode in common bean (Phaseolus vulgaris) was examined using an in vitro autotrophic tripartite culture system. Two in vitro assays were carried out with each of the nematode species. Each assay consisted of two treatments: the plants were either inoculated with the rhizobial strain or remained non-inoculated (control plants). To examine the effect of either pre- or simultaneous inoculation of the rhizobial strain on the reproduction of M. incognita and R. similis, one assay was carried out in which the nematodes were inoculated 3 weeks after rhizobial inoculation while another assay was carried out in which the nematodes were inoculated simultaneously with the rihizobial strain. Both pre-inoculation and simultaneous inoculation with R. etli CNPAF 512 significantly suppressed the reproduction of both M. incognita and R. similis.